Microbiological qualities of some foods sold in the street and in the mid-level and high-level restaurants - Asma Binte Afzal (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.